PENERAPAN TEKNOLOGI KOMUNIKASI MELALUI SISTEM INFORMASI MANAJEMEN DI PONDOK PESANTREN DARUL ARQOM KARANGANYAR - Nurdiana, Rita; Rokhimah, Anisa; Evi Yuliana, Margaretha (Penerbit Lafadz Jaya, 2023)
Advancements in communication technology in the field of education have greatly impacted the lives of students and organizations. The development of information management systems has helped organizations meet the needs of students by providing the information necessary for decision making and assisting organizations. This study used descriptive qualitative research and data collection from Darul Arqom Karanganyar Islamic Boarding School. Data analysis involves collecting all data from multiple sources, ensuring accuracy and consistency in research, and presenting results in research reports. Management information systems help parents access school information, registration, payment methods, and student tuition fees through various methods such as banks, ATMs, or mobile banking. However, some parents still have difficulty using this information system due to lack of technology and difficulties in financial transactions. To address this problem, strategies must be developed to help parents understand the functioning of internet information systems, as technology will continue to improve human work. The results of the research create efficient functions for stakeholders such as administration, teaching, guardians and staff.